A study on prevalence of risk factors of non-communicable diseases among undergraduate medical student - Yasmin, Shamima; Panja, Tanmay Kanti; Baur, Baijayanti (International Journal Of Community Medicine And Public Health, 2019)
Background: Non communicable diseases (NCDS) also referred to as “lifestyle diseases” are the leading cause of death globally. Most of the NCD risk factors are behaviorally acquired which are due to change in lifestyle during adolescent age groups With this in mind the present study was conducted with the following objective to determine the prevalence of risk factors of NCDS among medical undergraduates of a district of West Bengal. Methods: Cross-sectional observational study among 96 medical students of a medical college in a district of West Bengal using WHO STEPS questionnaire. Analysis of results was done by percentage and proportion. Results: A total of 96 students were interviewed and examined. Mean age was 19.3 years.12.5% were current smokers, 8.3% were alcohol users. 53.1% did no exercise. 46.5% female and 37.7% male had mild to moderate risk of high BMI, 51.2% female had abnormal waist circumference. 46.5% girls had abnormal waist hip ratio. 34.8% female and 35.8% males were pre hypertensive while 4% boys were hypertensive. Out of 22 students who had undergone blood test, 4.5% were early diabetic. 13.6% had borderline risk and 4.5% high risk for blood cholesterol. Conclusions: A high prevalence of risk factors for non-communicable diseases was found in the present study which emphasizes the need of interventions to reduce these risk factors among these future doctors.